Defect‐Induced Bound States in the Continuum Band of Metallic Nanobelts. Issue 5 (3rd October 2018) - Sánchez, Vicenta; Sánchez, Fernando; Wang, Chumin
Abstract : Bound states in the continuum (BICs) can be induced by structural defects or impurities and they have important applications in electronic and photonic devices, such as sensors with extremely high quality factor. A simple structure for the analysis of the electronic BICs could be two‐channel nanobelts with two central impurities. The nearest‐neighbor tight‐binding Hamiltonian of this structure is separable and one of the localized impurity states constitutes a BIC with null mobility. In this article, we study the localization and electrical conductivity of such BIC of a metallic belt with transition metal impurities. Significant changes in these two quantities are observed, when a small second‐neighbor hopping integral between the impurities and neighboring atoms is considered. The results of this study reveal the sensibility of such BICs to the short‐range hopping integrals in nanostructures. Abstract : Electronic bound states in the continuum (BICs) band of a two‐channel metallic nanobelt of 513 × 2 atoms with two transition metal impurities (black balls), through (a) density of states (DOS), (b) zero‐temperature DC conductance ( g ), and (c) participation ratio (PR) versus the chemical potential (µ) are investigated. The instability of such BICs under second‐neighbor hopping integrals is further analyzed.